2020
DOI: 10.1088/1757-899x/935/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

The residual stand damages due to log skidding using crawler tractor at one logging company in Central Kalimantan

Abstract: An investigation on residual stand damages due to log skidding using a skidding tractor was carried out at one logging company in Central Kalimantan in 2012. The objective is to find out information about residual stand damages on trees, poles, and sapling caused by Conventional Log Skidding (CLS system) and Low Impact Log Skidding (LILS system). Data on stand potency consists of tree, pole and sapling levels as well as the number of trees felled were collected. The investigation revealed that damage to the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Tree felling technique, which is performed properly in determining the felling direction and making the felling notch, is supposed probably to be able to reduce residual stand damage depending on slopes and stand densities. Low-impact logging system could reduce the damages of residual stand tree [8]. Mugasha et al [9] stated that selective cutting for fuel woods and logging are reported to be the main drivers of forest degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Tree felling technique, which is performed properly in determining the felling direction and making the felling notch, is supposed probably to be able to reduce residual stand damage depending on slopes and stand densities. Low-impact logging system could reduce the damages of residual stand tree [8]. Mugasha et al [9] stated that selective cutting for fuel woods and logging are reported to be the main drivers of forest degradation.…”
Section: Introductionmentioning
confidence: 99%